Quid pro quo? The future for graduate development programmes through the lens of talent management - Clark-Ambrosini, Jane L; Ashleigh, Melanie J.; Higgs, Malcolm; Baruch, Yehuda (International journal of human resource management, 2023)
The value of graduate development programmes (GDPs) from a talent management (TM) perspective is unknown. The contemporary TM literature focuses primarily on talent programmes for existing employees whereas less attention has been placed on externally recruited talent pools, in particular graduates. Attracting graduate talent is a priority for many organisations, as evidenced by the amount of investment contributed to this activity, but research on the employer's intended outcomes and expectations of participants in GDPs seems to lack coherence. To bridge this gap, this paper aims to develop a conceptual model to explicate the nature and process of GDP, using TM and the wider career literature. The model helps in our understanding of what contextual factors are important and how these factors influence policy and practice to GDPs. We also explore the value of GDPs based on the psychological contract perspective in a contemporary career system. To achieve these aims, the paper investigates how the design and agenda of GDPs may be reframed by analysing several literatures including talent pool segmentation, identity, psychological contract theory and career management. We also expand the existing TM literature by exploring the factors that directly impact the outcomes of GDPs and set future research agenda.